PENGARUH PENAMBAHAN FILLER SEMEN DAN LAMA PERENDAMAN AIR TERHADAP DURABILITAS LAPIS ASPAL BETON (LASTON) - Kosim Kosim; Zainuddin Muchtar (PILAR, 2013)
In this research, researcher tested material of Asphalt Concrete (AC) with coarse aggregate from Lahat and fine aggregate from Tanjung Raja South Sumatera, asphalt from Pertamina with Pen. 60/70,  while the filler material to be used is from Cement Baturaja. Proportion of filler to be used are 0%; 1,0%; 2,5%; and 4,0%. Marshall test results for each proportion of filler 0%, 1,0%, 2,5%, and 4,0% to the value of the KAO obtained 6,00%, 6,40%, 6,50% and 6,60%. Stability values respectively: 1225,67 kg, 1168,73 kg, 1187,60 kg, 1299,63 kg. Rated flow: 4,67 mm, 4,64 mm, 4,61 mm, 4,52 mm. VIM values obtained: 4,411%, 5,146%, 3,076% and 2,953%. VMA values obtained: 16,778%, 18,240%, 16,682% and 16,769%. VFA values obtained: 73,716%, 71,789%, 81,563%, 82,394%. Marshall Quotient: 262,77 kg / mm, 251,99 kg / mm, 257,54 kg / mm, and 287,88 kg / mm. Stability rest: 87,00%, 85,86%, 87,19% and 88,43%. The test results showed that while all Asphalt concrete mix with cement filler additive proposition to meet the criteria specified loss of stability due to immersion for 7 days is greater than 75%. From all asphalt concrete mixture obtained show that using the proportion of filler cement additive increase by 4% in asphalt concrete mix will increase the stability of the mixture, with a long soaking in water for 3 days. With the addition of additive filter using the proportion of cement by 4% in the asphalt mixture will be obtained concrete pavement material that can withstand heavy traffic load, during the service life of the road.